Analyzing the Impact of Bipolar Phase on the Use of the Words ‘Life’ and ‘Death’: a Study in the Survivor Community - Husaeni, Yesha Ashilla; Darma, Virga Putra (Language Circle: Journal of Language and Literature, 2024)
This study aims to analyze the impact of bipolar phases, namely manic and depressive phases, on the use of the words ‘life’ and ‘death’ in bipolar survivors’ communication. The research method used was qualitative with Likert scales to measure attitudes and perceptions towards stigma in the various bipolar phases. The results showed that bipolar phases influence survivors’ language use, where manic phases tend to produce positive connotations towards the word ‘life’ and depressive phases tend to produce negative connotations towards the word ‘life’. In addition, the social environment also influences how bipolar survivors perceive the use of these words. These findings support previous research on the impact of mood disorders on communication processes and provide additional insights into how bipolar phases influence word usage in the language of bipolar survivors.